2010
DOI: 10.3390/ijerph7031121
|View full text |Cite
|
Sign up to set email alerts
|

Food Patterns According to Sociodemographics, Physical Activity, Sleeping and Obesity in Portuguese Children

Abstract: Our study aimed to describe the association between food patterns and gender, parental education, physical activity, sleeping and obesity in 1976 children aged 5−10 years old. Dietary intake was measured by a semi quantitative food frequency questionnaire; body mass index was calculated and categorized according to the IOTF classification. Factor analysis and generalized linear models were applied to identify food patterns and their associations. TV viewing and male gender were significant positive predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
1
28

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 55 publications
5
71
1
28
Order By: Relevance
“…Sobre os fatores determinantes dos padrões "não saudáveis", estes estiveram associados ao menor nível de educação das mães 6,8,9 , a um maior tempo das crianças vendo televisão 9,11,26 , ao sexo masculino 26 , às crianças de pele branca, a um maior número de irmãos 6 , a filhos de mães com excesso de peso 8 , ao hábito de fumar dos pais, à presença de pais solteiros e, inversamente, a famílias de maior renda 11 .…”
Section: Tabela 3 -unclassified
See 1 more Smart Citation
“…Sobre os fatores determinantes dos padrões "não saudáveis", estes estiveram associados ao menor nível de educação das mães 6,8,9 , a um maior tempo das crianças vendo televisão 9,11,26 , ao sexo masculino 26 , às crianças de pele branca, a um maior número de irmãos 6 , a filhos de mães com excesso de peso 8 , ao hábito de fumar dos pais, à presença de pais solteiros e, inversamente, a famílias de maior renda 11 .…”
Section: Tabela 3 -unclassified
“…O padrão "tradicional" similar ao padrão típico brasileiro e denominado neste estudo de "dieta mista" foi associado ao sexo feminino 6,9,11 , às crianças com famílias não vegetarianas e cujas mães tinham um parceiro 8 , à maior escolaridade materna 9,10,26 , a famílias bem estruturadas, com pais casados, e inversamente associado com o tempo vendo televisão 11 e à maior duração do sono 26 .…”
Section: Tabela 3 -unclassified
“…The consumption of bread (r = 0.648), margarine (r = 0.627), Nescau®/Toddy® (r = 0.556) and milk and dairy products (r = 0.548) showed higher correlations with this AP, which probably explains why more frequent consumption of foods in this dietary pattern was significantly associated with increased odds of being overweight. Other research conducted with Portuguese [10] and Mexican [12] children and Australian [11] adolescents also observed an association between "unhealthy" dietary patterns and overweight.…”
Section: Discussionmentioning
confidence: 73%
“…This method may provide a better indicator of disease risk. Some research has identified an association between unhealthy dietary patterns and overweight [10] [11] [12], whereas other studies have found no consistent association [9] [13] [14].…”
Section: Introductionmentioning
confidence: 99%
“…Entre os principais fatores associados ao consumo alimentar não saudável, destacam-se: sexo masculino, menor nível socioeconômico e menor escolaridade [12][13][14] .…”
Section: N T R O D U ç ã Ounclassified